How CIOs interact with external peer networks : an application of grounded theory in an Irish private sector context - Davis, Brian Edward (Trinity College (Dublin, Ireland). Trinity Business School, 2010)
Interactions with peers have been identified, in the IS management literature, as being the most influential source of external contact for the Chief Information Officer (CIO), supporting them in their role as the most senior Information Systems (IS) executive in the organisation. Today, due to the strategic importance of IS to the operations and competitive position of many organisations, the CIO often operates as a key member of the top management team. At the centre of this role, the literature suggests, is the ability of the CIO to identify relevant strategic IS knowledge in the external technological environment, via their external boundary spanning activities, that can impact on the organisation’s strategic positioning and overall success. However, whilst the IS management literature identifies interactions with peers as being the most influential source of external contact available to CIOs, it fails to identify why they are such an important support to the CIO, or for that matter, how CIOs actually interact with such external peers. Similarly, a review of the wider management literature, whilst confirming the reasons why top management executives, such as the CIO, favour interactions with peers, it again fails to clarify how such executives, in fact, actually interact with peers, via contacts in external networks. Consequently, this leads to a clear gap in our knowledge and understanding relating to one of the key activities of the modern day CIO. For that reason, this research study will explore “how CIOs interact with external peer networks”.
Keywords: Business Studies Ph.D.; Ph.D. Trinity College Dublin